First Symptoms of Primary Progressive Aphasia and Alzheimer's Disease in Brazilian Individuals - dos Reis, Talita Gallas; Machado, Thais Helena; Caramelli, Paulo; Scornavacca, Francisco; Fernandez, Liana Lisboa; Beber, Bárbara Costa (Frontiers in Neurology, 2021)
Background: Primary Progressive Aphasia (PPA) is characterized by progressive language impairment due to focal degeneration of brain areas related to linguistic processing. The detection and differential diagnosis of PPA can be difficult with clinical features that may overlap with features of other neurological conditions, such as Alzheimer’s disease (AD). The scientific production on PPA in Latin American patients is still scarce. This study investigated the first symptoms in a Brazilian sample of patients with PPA in comparison with AD patients. Method: We compared the first symptoms reported by family members or caregivers of people with PPA (n=20; semantic variant n=8, non-fluent variant n=7, logopenic variant n=3, and unclassified cases n=2) and AD (n=16). Data were collected through the application of a structured questionnaire that was presented in an interview format to the family member or caregiver who knew the patient best. Results: Anomia, paraphasias and motor speech difficulties were the first symptoms capable of differentiating patients with PPA from those with AD, while memory was exclusive of AD. Among the PPA variants, anomia was the initial symptom associated with the semantic variant, while motor speech difficulties were associated with the non-fluent variant. The results are discussed considering the unique cultural and sociodemographic characteristics of this studied population. Conclusion: This study demonstrated that some of the initial symptoms of PPA patients may be unique to clinical variants of PPA and of AD, and their investigation may be useful for the early and differential diagnosis of this population.